2021
DOI: 10.3390/socsci10060235
|View full text |Cite
|
Sign up to set email alerts
|

“You Know Baseball? 3 Strikes”: Understanding Racial Disparity with Mixed Methods for Probation Review Hearings

Abstract: Prior literature on judicial decision-making post-sentencing is relatively scarce, yet with the growth of problem-solving courts and offenders placed on probation, judges are responsible for overseeing compliance of offenders beyond traditional decision-making points. More recently, scholars have called for more nuanced methods of examining judicial decision-making, disparity, and attribution than traditional quantitative methods. This study examines the factors that influence judicial sanctioning of probation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Our findings are similar, in that violating sobriety orders increased the odds of recidivism. Taken together, our findings suggest that underlying drug and alcohol abuse issues are associated with both noncompliance while under supervision (thus resulting in increased likelihood of sanctions) and recidivism (see Romain Dagenhardt, 2021). We do not have information on whether the offender was using drugs or alcohol at the time of the offense to fully parse out the direct influence of substance abuse, however, research has demonstrated its impact on the risk of domestic violence (Cafferky et al, 2018; Hirschel et al, 2010; Humphreys et al, 2005) and offending more broadly (e.g., Wilson et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…Our findings are similar, in that violating sobriety orders increased the odds of recidivism. Taken together, our findings suggest that underlying drug and alcohol abuse issues are associated with both noncompliance while under supervision (thus resulting in increased likelihood of sanctions) and recidivism (see Romain Dagenhardt, 2021). We do not have information on whether the offender was using drugs or alcohol at the time of the offense to fully parse out the direct influence of substance abuse, however, research has demonstrated its impact on the risk of domestic violence (Cafferky et al, 2018; Hirschel et al, 2010; Humphreys et al, 2005) and offending more broadly (e.g., Wilson et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…We then supplement these data with interviews with judges and prosecutors to illuminate the decision-making processes that lead to pretrial detention and incarceration for citizen and noncitizen defendants. In research on disparity in court processing, studies applying such mixed-methods are rare (Romain Dagenhardt, 2021) because most studies only rely on official data from standardized case files (Wermink et al, 2017). Our qualitative component responds to recent calls for mixed-methods approaches in sentencing research (Gaub & Holtfreter, 2015;Romain Dagenhardt, 2021), and in doing so, our study advances the literature by not just noting imprisonment differences by citizenship status, but by illuminating the potential processes driving these disparities.…”
Section: Introductionmentioning
confidence: 84%
“…While men in substance-disorder treatment programs are often pushed toward job readiness programs to become the “average Joe taxpayer” (Gowan and Whetstone 2012; see also Halushka 2020), women are more typically instructed to resolve flawed desires, emotions, and family relationships, sometimes with the additional goal of workforce participation (Haney 2010; Wyse 2013; Leverentz 2014; McKim 2014, 2017; Gurusami 2017; Kerrison 2018a). Programs are also racialized, attempting to mold Black and Latino/a/x populations into a white middle-class norm, placing responsibility for the effects of racism onto racialized people while reading (and treating) white people’s drug use through more sympathetic medical lenses (Miller 2014; Gurusami 2017; McKim 2017; Whetstone and Gowan 2017; Dagenhardt 2021; Lindsay and Vuolo 2021).…”
Section: Conceptual Backgroundmentioning
confidence: 99%